The Application of Project-Based Learning in the Independent Curriculum to Increase Student Creativity in PAI Subject at School - Novita Ayu Utari; Irma Soraya; Asep.S. Hamdani (Edumaspul: Jurnal Pendidikan, 2024)
This study is founded on the fact that students' low learning activities in class during the teaching and learning process are a reality in the world of education. Many students were unable to fully complete the project assignments that the teacher gave them. In order to develop students who have critical, active, and creative thinking, the project based learning (PjBL) learning paradigm promotes students to gain new insights and information based on each individual's experience. In order to ascertain the success of the application of the project based learning (PjBL) learning model in teaching Islamic Religious Education and Character at the high school level, a literature study (library research) was employed as the method of research in this article. The researcher first formulates the research problem before moving on to locating prior, pertinent research as the basis for their analysis. This study is based on the observation that in the world of education, low levels of student learning activities during the teaching and learning process are a reality. keywords project based learning, Islamic religious education and character